Topical Issues of the Need for Digitalization of the Banking System in the Republic of Uzbekistan - Azimova Shakhnoza Samukjanovna; Khamrokhuzhaeva Sitora (Genius Journals, 2022)
The digitalization of the economy is an important step in providing remote financial services to the population, which not only improve the quality of life of the population, but also contribute to the country's further integration into world processes. This article considers the legal framework of the Republic of Uzbekistan as a foundation for the introduction of innovative financial services in the activities of commercial banks in the country. At the same time, the activities of the Central Bank carried out in accordance with the Development Strategy of New Uzbekistan and other legislative acts are significant in the transformation of the economy
Keywords: Digitalization; commercial banks; online banking; transformation